2015
DOI: 10.1371/journal.pone.0119340
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Probe Flexibility and Gelatin Embedding on Neuronal Density and Glial Responses to Brain Implants

Abstract: To develop long-term high quality communication between brain and computer, a key issue is how to reduce the adverse foreign body responses. Here, the impact of probe flexibility and gelatine embedding on long-term (6w) tissue responses, was analyzed. Probes of same polymer material, size and shape, flexible mainly in one direction, were implanted in rat cerebral cortex (nimplants = 3 x 8) in two orientations with respect to the major movement direction of the brain relative to the skull: parallel to (flex mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 26 publications
1
37
0
Order By: Relevance
“…3F and H) could possibly be explained by a previous study reporting that a rigid cylindrical implant tethered to the skull caused oval scarring [97]. The author suggested the principle direction of brain movement relative to the skull of freely moving rodents may strongly influence the tissue response and the principle direction of brain movement caused more pressure to the cell body shape towards that direction [98]. Our analyses using automated algorithms confirmed that the neurons around the stiff implant had a much higher CSSI than those around the soft wires, and the CEA of cell body deformation was well aligned with predicted strain direction.…”
Section: Discussionmentioning
confidence: 99%
“…3F and H) could possibly be explained by a previous study reporting that a rigid cylindrical implant tethered to the skull caused oval scarring [97]. The author suggested the principle direction of brain movement relative to the skull of freely moving rodents may strongly influence the tissue response and the principle direction of brain movement caused more pressure to the cell body shape towards that direction [98]. Our analyses using automated algorithms confirmed that the neurons around the stiff implant had a much higher CSSI than those around the soft wires, and the CEA of cell body deformation was well aligned with predicted strain direction.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro cell viability studies pertaining to mechanotransduction also suggested that excessive strain conditions decrease neuronal viability [15], whereas soft substrates allow for preferential attachment and growth of neurons over glial cells [16]. Based on these initial findings, many groups shifted gears toward developing probes made of softer materials than silicon, including polyimide [8,17], parylene [18,19], SU-8 [20,21], nanocomposites [14,[22][23][24], and other materials [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that gelatin can be used as a coating-material to provide structural support during implantation of ultrathin flexible electrodes in the brain [5,33] and that gelatin itself can significantly reduce microglia activation but not the astrocytic response [4,6]. Here we developed a novel method for local delivery of nanoparticles from gelatin coatings allowing the amount of drug to be kept several orders of magnitude lower as compared to systemic administration.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the mechanical properties, such as flexibility, size, anchoring and specific weight of the electrodes are of key importance [2][3][4][5]. However, it was only when combining ultra-flexible mechanical properties with a gelatin embedding that the ubiquitous loss of nearby neurons was, for the first time, abolished [4]. Moreover, we recently found that gelatin coating promotes healing of the blood-brain barrier [6].…”
Section: Introductionmentioning
confidence: 99%